Influence of Corporate Governance and Accounting Mechanisms on Aggressive Revenue Recognition in Chevron Oil and Gas Industries in Nigeria (2010–2024) - emmanuel okporo; Moses Agashi Aloh; Sylvanus Nwosulor Ugamah (Sekolah Tinggi Manajemen IPMI, 2026)
This study examines the influence of corporate governance accounting mechanisms on aggressive revenue recognition in Chevron Nigeria Limited (CNL) and its subsidiaries. Adequate Administrative Performance served as the non-predictable variable representing corporate governance accounting mechanisms, while Socio-Economic Growth and Development was used as the predictable variable representing aggressive revenue recognition. The study focused on four dimensions: audit committee, staffers’ skill, monitoring technique, and evaluation exercise. A retrospective (ex-post facto) research design was employed using panel data from nine Chevron subsidiaries, including the parent company, covering the period 2010–2024. Data were analyzed using EViews 12 with Ordinary Least Squares (OLS) regression and the Hausman test to determine the most appropriate estimation model. The random effects model was selected for hypothesis testing. The findings indicate that audit committee effectiveness, staffers’ skill, and monitoring technique have significant positive effects on adequate administrative performance, while evaluation exercise has a positive but statistically insignificant effect. The study concludes that effective corporate governance accounting mechanisms enhance administrative effectiveness and efficiency in Chevron Nigeria Limited and its subsidiaries. It recommends strengthening monitoring techniques to improve operational performance and facilitate the timely identification of deficiencies and best practices.